Effect of nitrogen fertilizer, heading date, and pollination speed on the seed production of fifth‐generation rice. (20th March 2020) - Huang, Yifeng; Wu, Pingfan; Zeng, Hao; Du, Longgang; Wang, Meixing; Guo, Shaoying; Xie, Qingjun
Abstract: Production of hybrid seed is a crucial limiting factor for the commercial development of hybrid rice. Studies have shown that the seed production of japonica‐type or indica‐type hybrid rice is affected by many factors, Japonica‐type or indica‐type hybrid rice are considered as third‐generation rice. However, little is known about japonica‐indica hybrid rice, which is a fifth‐generation (5G) rice. We evaluated the effects of multiple cultivation approaches to improve seed production of 5G rice. Our results showed that application of 300 kg ha –1 resulted in the optimal seed setting ratio when compared with higher N rates. In addition, we found that the heading date of the two elite sterile lines accelerated under late sowing, which facilitated establishment of hybridization between the parent lines. Moreover, our results demonstrated that proper heading date is a crucial factor for seed setting of the test male sterile lines, Zhe 04A and Chunjiang 16A. We also found that the faster pollination speed, the more seeds of 5G rice were obtained. We propose that the combination of applications would significantly reduce the cost and increase the efficiency of producing 5G rice seed.